PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMILIH JURUSAN PADA PERGURUAN TINGGI NEGERI - Yeka Hendriyani; Nabila Azzahra Shammi (Jurnal Teknologi Informasi dan Pendidikan, 2016)
This research aims to design a Decision Support System (DSS) to choose a major in public universities. The system can be used asr consultation tool for prospective students in determining the choice of majors and colleges that match their interests and academic abilities. The input data used are interest test results and academic ability test then the data will be processed using Case Based Reasoning (CBR) to match the psychology and a passing grade score in appropriate department at public universities. This system is designed using the Unified Modelling Language (UML) design model, the PHP programming language with laravel framework, and MySQL as the database. Results from this study is an application that can be used prospective students or class XII students in SMA / SMK to consult in determining by of majors in higher education.